Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.12788/jhm.3097
|View full text |Cite
|
Sign up to set email alerts
|

Less Lumens‐Less Risk: A Pilot Intervention to Increase the Use of Single‐Lumen Peripherally Inserted Central Catheters

Abstract: To reduce risk of complications, existing guidelines recommend use of peripherally inserted central catheters (PICCs) with the minimal number of lumens. This recommendation, however, is difficult to implement in practice. We conducted a pilot study to increase the use of single‐lumen PICCs in hospitalized patients. The intervention included (1) education for physicians, pharmacists, and nurses; (2) changes to the electronic PICC order‐set that set single lumen PICCs as default; and (3) criteria defining when u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 33 publications
3
35
0
1
Order By: Relevance
“…66,76 Evidence evaluating multilumen PICC outcomes was mixed. One study found DVT risk increased with $2 lumens, 67 another study reported a nonsignificant reduction in CLABSI risk with single-lumen use, 39 while a number of other studies reported that PICC lumen number was not significantly associated with the risk of thrombosis 81,122 or infection. 81 Overall, most studies found occlusion was the most common complication associated with catheter lumen number, and $2 lumen PICCs were associated with the highest risk of occlusion.…”
Section: Device Lumensmentioning
confidence: 99%
See 1 more Smart Citation
“…66,76 Evidence evaluating multilumen PICC outcomes was mixed. One study found DVT risk increased with $2 lumens, 67 another study reported a nonsignificant reduction in CLABSI risk with single-lumen use, 39 while a number of other studies reported that PICC lumen number was not significantly associated with the risk of thrombosis 81,122 or infection. 81 Overall, most studies found occlusion was the most common complication associated with catheter lumen number, and $2 lumen PICCs were associated with the highest risk of occlusion.…”
Section: Device Lumensmentioning
confidence: 99%
“…81 Overall, most studies found occlusion was the most common complication associated with catheter lumen number, and $2 lumen PICCs were associated with the highest risk of occlusion. 28,39,81 Similarly, studies reported mixed outcomes on the basis of CVAD lumen number. Two studies reported no association between single-and double-lumen catheters and rates of infection 65 and major CVAD-related complications, 26 whereas others reported higher rates of CLABSI, 46,106 exit-site or tunnel infection, 46 malfunction or occlusion, 46 and complications requiring repositioning 26 for doublelumen CVADs.…”
Section: Device Lumensmentioning
confidence: 99%
“…Since publication, MAGIC has been implemented in many hospitals worldwide but particularly in the United States, with evidence suggesting significant reductions in inappropriate VAD use, patient harm, and costs. [9][10][11] Similar evidence-based VAD appropriateness criteria have not been developed for pediatrics. Therefore, we sought to develop the Michigan Appropriateness Guide for Intravenous Catheters in pediatrics (miniMAGIC), a pediatric-focused version of its adult counterpart, using the RAND Corporation and University of California, Los Angeles (RAND/ UCLA) Appropriateness Method 12 to address this knowledge gap.…”
mentioning
confidence: 99%
“…Additionally, we did not have data on direct cost or thrombosis rates, though we expect improvement based on the results of previous studies. 8,9 In conclusion, our intervention led to a significant and sustained decrease in the utilization of multilumen PICCs and a relative increase in utilization of single-lumen PICCs, with an associated downward trend in PICC-related CLABSI events. Future studies should be done across multiple sites to validate these findings with the statistical power needed to show expected improvements in clinical outcomes, particularly in infection and thrombosis and cost-effectiveness.…”
Section: Discussionmentioning
confidence: 74%